ASSESSMENT OF COMMUNITY AWARENESS AND PARTICIPATION TOWARDS ENVIRONMENTAL EDUCATION IN GOMBE METROPOLIS GOMBE STATE, NIGERIA - UMAR AHMAD, YUSUF; ADAMU, USMAN (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
This study attempts to assess community awareness and participation in environmental education in Gombe Metropolis, Gombe State Nigeria. The study used both primary and secondary sources of data. The primary data was generated from structured questionnaires administered and interviews while the secondary data was collected from published materials. The study area had projected population as about 391,869 people as at 2019. In view of that, stratified and cluster sampling techniques were employed to draw 250 respondents from the total population around the six major wards (Bolari, Pantami, Kumbiya-kumbiya, Jekadafari, Tudun- wada and Herwagana) in the study area. The findings of the study however, revealed that the level of environmental education and awareness among the people of the study area was moderate. The study further indicated that the people in study area exhibited some level of positive environmental attitudes such as use of dust-bin, waste disposal points, cleaning of culverts and drainages, etc. The study concluded that the overall people of the study area were aware of the environmental problems that exist in Gombe metropolis, but could not act positively. However, he major environmental problems highlighted by the respondents among others were, soil erosion, flooding, poor sanitation conditions deforestation, etc. The study finally recommended that efforts should be made by the government, NGOs and all other relevant stakeholders such as community/environmental health workers, community leaders, clerics, environmental marshals, etc in educating and enlightening communities about roles expected of them to play towards environmental awareness, protection, maintenance and conservation.